IT dan Pendidikan Distance Education - Safiq, Abdulloh (Ar-Rosikhun: Jurnal Manajemen Pendidikan Islam, 2022)
The distance education model has made a significant contribution to the history of distance education in Indonesia, despite the quality of the results, it is still the basis of controversial debates in this country. The significance of the contribution can be seen from the perspective of the number of students who live in rural areas and those who have financial problems can experience adequate education through distance education. The method in this paper is a literature study which is library research. Literature research is a series of activities related to library data collection methods. Literature study is also a theoretical study, references and other scientific literature related to culture, values and norms related to the social situation under study. From a historical perspective, distance education is seen from three phases of development; the introductory phase, from the 1950s to 1983, the socialization phase from 1984 to 1993, and the innovation phase from 1994 to the present. Correspondence studies and Palapa satellites were categorized as instructional delivery systems in the introductory phase, radio communication systems in the socialization phase, and cassettes, slide tape programs, videos, television, Nusantara 21 electronic communication systems, and video conferencing technology used to deliver instructional messages in this phase. innovation. Although various models of distance education such as study correspondence, Palapa satellite, radio communication systems, audio cassettes, slide programs, tapes, videos, television, electronic communication systems, and video conferencing technology have been applied in many subject matter.Keywords. Distance Education; E-Learning; Instructional Technology